HUBUNGAN PARITAS DENGAN DERAJAT LASERASI JALAN LAHIR DI POLINDES JETIS LOR KECAMATAN NAWANGAN KABUPATEN PACITAN - Etika Desi Yogi (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
For women, the perineum is very important stretching and lubricating the perineum during labor can weaken the pelvic floor muscles in the vaginal wall, trauma to the perineum also causes discomfort and pain during sexual intercourse and an estimated 85% of maternal mothers experience birth canal lacerations (Kettle and Tohil 2008). One of the fears that are often felt by pregnant women, especially third timers, is fear of being torn and afraid of sewing. Especially for mothers who have experienced it, this can make their own trauma when facing the birth process later (USU, 2006). The purpose of this study was to determine the relationship of parity to the degree of laceration of the birth pathway in Jetis Lor Polindes, Nawangan District, Pacitan Regency. The design or design in this study is correlation analysis, with the